Conceptual model of tacit knowledge transfer for PBL teaching method in system analysis and design course - Ahmad, Mazida; Zainol, Azida; Marzuki @ Matt, Zaharin; Muhd Darus, Norida; Baharom, Fauziah (Universiti Utara Malaysia, 2014)
Problem Based Learning (PBL) is a teaching method that is able to transfer tacit knowledge from lecturers to students based on Socialization, Externalization, Combination, and Internalization (SECI) model.However, the SECI model does not include students’ performance factor, which is an indicator to measure the effectiveness of teaching and learning processes.Hence, this study proposes a conceptual framework to evaluate the effectiveness of using PBL as a teaching method in transferring tacit knowledge by enhancing the SECI model.The methodology begins with constructing a questionnaire to investigate the SECI and Performance processes in transferring tacit knowledge from lecturers to students.The respondents are students of System Analysis Design (SAD) in Universiti Utara Malaysia (UUM). The gathered data were analyzed using Structural Equation Modeling (SEM) to identify the effect of the significant direct relationship among the factors.The findings reveal that the SECI model fits the data for PBL teaching method in Software Engineering (SE) education.Three significant direct effects (regression weights) were obtained between the factors of SECI model.However, the direct effects of SECI processes on performance of students are not significant. The findings of this study also evidence that the SECI model is partially present in the knowledge creation processes in the PBL teaching method for SE education.